2015
DOI: 10.1177/0267659115573280
|View full text |Cite
|
Sign up to set email alerts
|

Variation in duplex peak systolic velocity measurement in a multi-site vascular service

Abstract: We observed a significant level of error and variation in PSV measurements across four sites within our vascular network. Variation in instrumentation-related factors may be accountable for this. In light of the centralisation of vascular services, it is increasingly important to unify and implement scanning protocols in order to reduce error and inter-site variability.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

1
10
0

Year Published

2016
2016
2023
2023

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 8 publications
(11 citation statements)
references
References 21 publications
1
10
0
Order By: Relevance
“…In this study, reduced precision for VFI and SDUS was found in vivo compared to in vitro. This has also been reported for velocity estimations in the flow phantom with constant versus pulsatile flow 41 , as for in vitro estimation compared to in vivo 21 40 42 43 . The main reason for the difference in this study is probably that the in vitro flow was constant, while the in vivo blood flow was pulsatile.…”
Section: Discussionsupporting
confidence: 67%
“…In this study, reduced precision for VFI and SDUS was found in vivo compared to in vitro. This has also been reported for velocity estimations in the flow phantom with constant versus pulsatile flow 41 , as for in vitro estimation compared to in vivo 21 40 42 43 . The main reason for the difference in this study is probably that the in vitro flow was constant, while the in vivo blood flow was pulsatile.…”
Section: Discussionsupporting
confidence: 67%
“…Results from our study exhibited the discontinuity within our small sample similar to that found in the literature. The inability to unite a common method has led to significantly varied results . A multisite vascular network demonstrated there were still inconsistencies in Doppler angle methods showing the systemic spread of discontinuity into specialist communities .…”
Section: Discussionmentioning
confidence: 99%
“…The inability to unite a common method has led to significantly varied results . A multisite vascular network demonstrated there were still inconsistencies in Doppler angle methods showing the systemic spread of discontinuity into specialist communities . They stressed the importance of implementing and unifying scanning protocols to reduce error and intersite variations …”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations